The Semantic Network Model of Creativity: Analysis of Online Social Media Data. Issue 3 (2nd July 2016) - Yu, Feng; Peng, Theodore; Peng, Kaiping; Zheng, Sam Xianjun; Liu, Zhiyuan
Abstract : The central hypothesis of Semantic Network Model of Creativity is that creative people, who are exposed to more information that are both novel and useful, will have more interconnections between event schemas in their associations. The networks of event schemas in creative people's minds were expected to be wider and denser than those in less creative people's minds. Based on this theory, data from Chinese online social media, also known as "Weibo microblogging, " were analyzed. Each user's score consisted of the metric of coverage, which represented the spread of the network, as well as the metric of density, which represented the interconnections among nodes in the network. The results showed that occupations had a significant effect on people's creativity score. Academic scholars and writers in general had higher scores compared to other groups, such as entertainment celebrities and sport stars. The implications and limitations of this method of quantifying people's creativity were discussed.